2018
DOI: 10.1111/os.12397
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Clinical Results of Minimally Invasive Spinal Fusion Surgery in an Unselected Patient Cohort of a Spinal Care Unit

Abstract: Minimally invasive spinal surgery is a safe and effective treatment option and may be superior to open surgery in subpopulations with significant co-morbidities and risk factors, such as elderly and obese patients as well as patients with an active smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…A multicenter study found equivalent outcomes for obese patients having spinal MISS or open techniques [ 190 ]. Conversely, Senkar et al found minimally invasive surgical techniques had the highest utility in patients with multiple comorbidities [ 191 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study found equivalent outcomes for obese patients having spinal MISS or open techniques [ 190 ]. Conversely, Senkar et al found minimally invasive surgical techniques had the highest utility in patients with multiple comorbidities [ 191 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study found equivalent outcomes for obese patients having spinal MISS or open techniques (188). Conversely, Senkar et all found minimally invasive surgical techniques had the highest utility in patients with multiple comorbidities (189). There is evidence that minimally invasive surgical approaches improve pain scores, decrease opioid consumption and decrease length of stay, when used within the appropriate clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that decreased bone graft volume decreases the mass, which consolidates into a thick bone mass and in turn fails to significantly increase the fusion mass (5,7,13). Conversely, increasing the bone graft volume has been demonstrated to induce extensive bone resorption, which in turn decreases the bone matrix for new bone construction, resulting in failure of spinal fusion (14). Thus, the bone graft volume and structural changes essentially determine the fusion rate success.…”
Section: Discussionmentioning
confidence: 99%